Como reír tarde : una aproximación a la inexactitud en la obra de Dennise Vaccarello - Piñeiro, Manuel Mata (2018)
This article explains the foundations of an artistic attitude based on aspects such as the error and as the inaccuracy, highlighting the creative impulse that prompts the moment and the need for an alternative definition in the language that composes and conditions the work. All this is exemplified by the snapshot series of Dennise Vaccarello, titled “As laughing later”